Serum antioxidant enzyme levels are decreased in patients with urinary calcium oxalate stones - Cakir, Omer Onur; Culha, Mehmet Gokhan; Arisan, Serdar; Arisan, Elif Damla; Altin, Murat; Ward, Sam; Zengi, Oguzhan; Ergenekon, Erbil (Urology Journal, 2017)
Purpose: To compare the serum antioxidant enzyme levels between patients with urinary stone disease and healthy volunteers to determine the effect of cellular oxidative stress on urinary calcium oxalate stones formation. Materials & Methods: A total of 51 patients with proven urinary calcium oxalate stones (female 35.3%, mean age: 49.3 years) and 37 healthy subjects (female 45.9%, mean age: 44.1 years) were included. The serum levels of antioxidant catalase, glutathione peroxidase, superoxide dismutase and lipid peroxidation were measured in serum samples taken from the peripheral venous circulation. Results: Mean serum catalase level of patient group was insignificantly higher than healthy subjects (7.54 mmol- H2O2/mg/sec versus 6.16 mmolH2O2/mg/sec, respectively; P = .06) whereas mean superoxide dismutase level (1.56 U/ml versus 3.86 U/ml, P = .047), glutathione peroxidase level (6.70 U/ml versus 8.19 U/ml, P = .022) and lipid peroxidation level (2.35 nmol/ml versus 3.31 nmol/ml, P = .034) of patient group were significantly lower than healthy subjects. Patients with family history of urinary stone disease had significantly lower mean serum levels of catalase (P = .037), superoxide dismutase (P = .047) and glutathione peroxidase (P = .01), compared with patients without family history. Conclusion: The findings of this study provide evidence regarding the role of oxidative stress in the development of urinary calcium oxalate stones. Future clinical trials are necessary to elucidate the actual mechanisms of the calcium oxalate stone formation in the environment with increased oxidative stress.